No association of natural killer cell number and function in peripheral blood with overweight/obesity and metabolic syndrome in a cohort of young women. Issue 4 (18th February 2022) - Keilen, Julia; Gar, Christina; Rottenkolber, Marietta; Fueessl, Louise U.; Joseph, Anna T.; Draenert, Rika; Seissler, Jochen; Lechner, Andreas
Abstract: Aim: To reexamine the associations of NK cell number and function in the peripheral blood with overweight/obesity and the metabolic syndrome in a large, well‐phenotyped human cohort. Methods: Cross‐sectional analysis of 273 women in the PPSDiab Study; measurement of absolute and relative number of NK cells in peripheral blood, and of functional parameters CD69 positivity and cytotoxicity against K562 cells; group comparison of NK cell characteristics between lean, overweight, and obese participants, as well as metabolic syndrome scores of 0, 1, 2, and ≥3; Spearman correlation analyses to clinical parameters related to the metabolic syndrome. Results: We found no differences in NK cell number and function between lean, overweight, and obese women (relative NK cell number (median (Q1–Q3), [%]) 5.1(2.6–9.4) vs. 4.8 (2.9–8.4) vs. 3.8 (1.7–7.8), p  = 0.187; absolute NK cell number [10 6 /L]: 86.9 (44.6–188.8) vs. 92.6 (52.5–154.6) vs. 85.9 (44–153.8), p  = 0.632; CD69+ [%]: 27.2 (12.9–44.3) vs. 37.6 (13.2–52.8) vs. 33.6 (16.3–45), p  = 0.136; cytotoxicity [%]: 11.0 (7.1–14.5) vs. 8.5 (6.4–13.2) vs. 11.3 (8.7–14.2), p  = 0.094), as well as between different metabolic syndrome scores. Nonesterified fatty acids correlated with absolute and relative NK cell number and cytotoxicity ( ρ [ p ‐value]: 0.142 [0.021], 0.119 [0.049], and 0.131 [0.035], respectively). Relative NK cell number further correlated with high‐density lipoprotein cholesterol (0.144 [0.018]) and cytotoxicity with 2 h glucose in oral glucose tolerance testing (0.132 [0.034]). CD69 positivity correlated with body fat (0.141 [0.021]), triglycerides (0.129 [0.033]), and plasma leptin (0.155 [0.010]). After correction for multiple testing, none of the associations remained significant. Conclusion: In the present study, we observed no associations of NK cell number and function in the peripheral blood with overweight/obesity and the metabolic syndrome. Extreme phenotypes of obesity and the metabolic syndrome might have caused differing results in previous studies. Further analyses with a focus on compartments other than peripheral blood may help to clarify the relation between NK cells and metabolic diseases. Abstract : Contrary to previous, population‐based studies, NK cell number and function in the peripheral blood are not altered with overweight/obesity or the metabolic syndrome in a cohort of premenopausal women. Obesity‐associated immune dysfunction may therefore be less pronounced in this segment of the population.